Business Intelligence Dashboard Visualization on Information Systems for Online Verification of Invoice Documents and Requests for Goods or Services - Hadiwinata, Daad; Fauziah, F; Mardiani, Eri (STIKOM Tunas Bangsa Pematangsiantar, 2024)
In the daily running of their business, business companies are usually faced with the problem of adapting to changing trends related to the business world. To make a decision that is precise, fast, and accurate based on data and analysis, the company must apply Business Intelligence (BI) based technology. In this research, the study was conducted at PT ADHI KARYA (Persero) Tbk, which has a problem with the document verification system which is still done manually. To help the above problems, a solution is offered by utilizing Business Intelligence (BI) based technology to create a dashboard of information systems for verification of invoice documents and requests for goods and services online. For evaluating the performance of employees or verifier officers can use the collaboration between BI and the K-Means Algorithm by classifying incoming data based on the duration of the data input until the e-Verification sheet is sent by the system. The system development method in this study uses the RAD (Rapid Application Development) method of rapid application development. Which is expected to produce a solution in the form of a visualization dashboard for online verification information systems for invoice documents and requests for goods and services based on Business Intelligence technology.